Cultivating Creativity in Methodology and Research In Praise of Detours (Palgrave Studies in Creativity and Culture, 2018)
This book presents a variety of narratives on key elements of academic work, from data analysis, writing practices and engagement with the field. The authors discuss how elements of academic work and life - usually edited out of traditional research papers - can elicit important analytical insight. The book reveals how the unplanned, accidental and even obstructive events that often occur in research life, the 'detours', can potentially glean important results. The authors introduce the process of 'writing-sharing-reading-writing' as a way to expand the playground of research and inspire a culture in which 'accountable' research methodologies involve adventurousness and an element of uncertainty. Written by scholars from a range of different fields, academic levels and geographic locations, this unique book will offer significant insight to those from a range of academic fields.